Extraction and characterisation of Cerbera odollam seed oil as a potential plant-based corrosion inhibitor / Nor Roslina Rosli ... [et al.] - Rosli, Nor Roslina; Abdullah, Izyan Syifaa; Mohd Rosli, Nur Adryna; Zulbakeriamerudin, Nurul Nadiah (Universiti Teknologi MARA Shah Alam, 2023)
Certain types of commercial corrosion inhibitors consist of a specific, tannic acid-derived compounds. Tannin compounds are antioxidants and widely found in many species of plants. In this works, oil from the seeds of the poisonous fruit, sea mango (Cerbera odollam), was seen as a potential candidate for a natural corrosion inhibitor. The oil was extracted via solvent extraction using a Soxhlet extractor for 6 hours at varying temperatures between 100 to 200 °C. The solvents used were hexane and methanol. Structural characterisation of active corrosion inhibition compounds in the oil samples was analysed using Fourier Transform infrared spectroscopy (FTIR) and Gas Chromatography Mass Spectroscopy (GC-MS). Thermogravimetric analysis (TGA) was done to determine the seed oil's thermal stability and decomposition temperature. The highest extraction yield was found using hexane as the solvent at 150 °C. TGA results indicated that the oil was stable at temperatures below 200 °C. The presence of carboxylic acids, as evidenced by the FTIR and GC-MS analysis, indicated possible corrosion-inhibitive properties of the extracts. Phytochemical screening tests revealed that tannin, saponin, phenol, and steroid were present in the sea mango seed oil while flavonoid was undetected.